2022
DOI: 10.1155/2022/2288961
|View full text |Cite|
|
Sign up to set email alerts
|

Cloud Computing: Legal Issues and Provision

Abstract: Micro, Small, and Medium Enterprises (MSMEs) are gradually adopting cloud-based solutions using Information, Communication, and Technologies (ICT). Due to the lack of awareness regarding the legal challenges arising from jurisdictional issues of the Cloud Service Provider (CSP), MSMEs often get entangled in expensive litigations. The paper throws light on such legal conflicts and proposes new innovative ways (such as bilateral treaties, US CLOUD Act, Mutual Law Assistance Treaties, and In-house Capability) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Ref. [15] found that the organization's limited knowledge of cloud computing technology acted as a challenge. In the context of secure cloud computing, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [15] found that the organization's limited knowledge of cloud computing technology acted as a challenge. In the context of secure cloud computing, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%